Paraglomus occidentale, a new arbuscular mycorrhizal fungus from the sources of the Amazon river in Peru, with a key to the Paraglomeromycetes species. - Corazon Guivin, Mike Anderson; Cerna Mendoza, Agustín; Guerrero Abad, Juan Carlos; Vallejos Tapullima, Adela; Ríos Ramírez, Orlando; Vallejos Torres, Geomar; De la Sota Ricaldi, Ana María; Santos, Viviane Monique; Alves da Silva, Gladstone; Oehl, Fritz (Verlag Berger, 2020)
A new arbuscular mycorrhizal fungus, Paraglomus occidentale, was found in an agricultural plantation of the inka nut (Plukenetia volubilis) in the Amazonia region of San Martín State in Peru. The inka nut was grown in mixed cultures together with Zea mays and Phaseolus vulgaris. The fungus was propagated in bait and single species cultures on Sorghum vulgare, Brachiaria brizantha, Medicago sativa and P. volubilis as host plants. The fungus differentiates hyaline spores terminally on cylindrical to slightly funnel-shaped hyphae, singly in soils or rarely in roots. The hyaline spores have a triple layered outer wall and a bi- to triple-layered inner wall. They are (59)69–84(92) µm in diameter. The new fungus is distinguished from all other known Paraglomus spp. by spore wall structure including staining characteristics in Melzer’s reagent, which is yellow-grayish to grayish on the outermost and generally dark yellow on the second spore wall layer. Phylogenetically, the new fungus is recognized in a well-separated clade, near to P. laccatum and P. occultum. Finally, an identification key to the Paraglomeromycetes species is included comprising all known species of the genera Paraglomus, Innospora and Pervetustus.